2021
DOI: 10.1186/s12960-021-00603-1
|View full text |Cite
|
Sign up to set email alerts
|

Shaping applied epidemiology workforce training to strengthen emergency response: a global survey of applied epidemiologists, 2019–2020

Abstract: Background Rapid and effective emergency response to address health security relies on a competent and suitably trained local and international workforce. The COVID-19 pandemic has highlighted that the health security workforce needs to be well equipped to tackle current and future challenges. In this study, we explored whether training in applied epidemiology was meeting the current needs of the applied epidemiology workforce. Method We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Earlier research into the training gaps identified key areas for workforce support programs such as FETPs to focus on strengthening local workforces [ 2 ]. Other workforce support research has identified mentorship-type support helps to mitigate inexperience of the response workforce especially when navigating complex political environments [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier research into the training gaps identified key areas for workforce support programs such as FETPs to focus on strengthening local workforces [ 2 ]. Other workforce support research has identified mentorship-type support helps to mitigate inexperience of the response workforce especially when navigating complex political environments [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research shows a broad range of communication challenges. In a recent study of epidemiology training needs, communication skill development was identified as in need of strengthening [ 2 ]. To improve the effectiveness of the epidemiology workforce during emergency response, communication strategies need to be developed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations